Courts, justice and efficiency : a socio-legal study of economic rationality in adjudication - Fix Fierro, Héctor (Hart Pub., 2003)
This study explores the socio-legal context of economic rationality in the legal and judicial systems. It examines the meaning and relevance of the concept of efficiency for the operation of courts and court systems, seeking to answer questions such as: in what sense can we say that the adjudicative process works efficiently? What are the relevant criteria for the measurement and assessment of court efficiency? Should the courts try to operate efficiently and to what extent is this viable? What is the proper relationship between 'efficiency' and 'justice' considerations in a judicial proceeding? To answer these questions, a conceptual framework is developed on the basis of empirical studies and surveys carried out mainly in the United States, Western Europe and Latin America. Two basic ideas emerge from it. First, economic rationality has penetrated the legal and judicial systems at all levels and dimensions, from the level of society as a whole to the day-to-day operation of the courts, from the institutional dimension of adjudication to the organizational context of judicial decisions. Far from being an alien value in the judicial process, efficiency has become an inseparable part of the structure of expectations we place on the legal system. Second, economic rationality is not the prevalent value in legal decision-making, as it is subject to all kinds of constraints, local conditions and concrete negotiations with other values and interests.